Application and evaluation of traditional garden culture in modern urban landscape design under the context of cultural sustainability - XiaoXi Zhao; Rohayah Binti Che Amat (PLoS ONE, 2025)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) views cultural diversity as a core driver of sustainable development. Traditional garden culture, as an essential component of Chinese culture, encompasses rich historical significance and unique aesthetic values. Integrating elements of traditional garden culture into modern urban landscape design can enhance the cultural depth of urban spaces and increase the attractiveness and cultural identity of urban environments, thereby fostering sustainable urban development. In this context, this study proposes a method framework for the innovative design and evaluation of urban landscapes. Urban public landscape streetlights are used as a case study. First, the Grounded Theory (GT) and the Analytic Hierarchy Process (AHP) are combined to construct its hierarchical model of design evaluation indicators, and the weights and priority rankings of these indicators are calculated. Based on the AHP analysis results, the study draws inspiration from the traditional garden cultural elements of the Jinci Temple in Shanxi to carry out an innovative design practice for local urban landscape streetlights. Finally, the Fuzzy Comprehensive Evaluation (FCE) method is employed to assess and select the design proposals. This study explores the application and evaluation methods of traditional garden culture in modern urban landscape design based on the GT-AHP-FCE framework. The feasibility and effectiveness of this framework are validated through design examples, providing innovative theoretical and practical guidance for future designers and offering new pathways for the inheritance and innovation of traditional garden culture.